Modeling pore wetting in direct contact membrane distillation—effect of interfacial capillary pressure - Ahmad, S. N. A.; Matsuura, Takeshi; Jaafar, Juhana; Jiang, L. Y.; Ismail, A. F.; Othman, M. H. D.; A. Rahman, Mukhlis (Frontiers in Membrane Science and Technology, 2024)
This study aimed to develop a model for computing the direct contact membrane distillation (DCMD) performance, incorporating capillary pressure effects at the liquid/gas interface within membrane pores. At the steady state, the transport of the liquid phase and the gas phase was balanced. Using the developed simulation model, we explored how pore radius, feed/permeate temperature, pressure, and contact angle affected the distance of liquid intrusion into the pore, the weight flow rate in a single pore, and the temperature at the liquid/gas interface. The results of the model simulations agreed with the trends observed in the experimental DCMD flux data by many authors, particularly those regarding the effects of feed and permeate temperature and the effect of contact angle. Regarding the effect of feed pressure, the model predicted that the permeation rate decreased with an increase in the feed pressure when the permeate pressure was kept constant and also when the pressure difference between feed and permeate was kept constant. Concerning the effect of the permeate pressure, the model predicted that the permeation rate increased with an increase in the permeate pressure when the feed pressure was kept constant. The model also indicated that partial pore wetting was enhanced with an increase in feed pressure when the pore size was as large as 1 μm but diminished when the pore size was as small as 0.1 μm. According to the model, partial pore wetting diminished with a decrease in the permeate pressure. These trends, predicted by the model computations, were further compared with the experimental data recorded in the literature. and exits from the pore outlet in either vapor or condensed form. The membrane material needs to be hydrophobic to prevent liquid water from entering the pore. MD finds applications in desalination of sea-and brackish water and treating concentrated brine from the reverse osmosis (RO) process (Rácz et al., 2014;Ibrar et al., 2022). Despite its impressive performance, commercialization faces challenges due to pore wetting, causing a significant decrease in MD flux and selectivity (